American Studies in Spain: Recent trends. - HILTON, SYLVIA L (American Studies International)
Presents a list of humanities studies on the United States published in Spain. Lack of real American studies tradition in Spain; Historical studies concerning the connection of US with Spain; Experiences of hispanic minority groups in US; Native People of North America; Works on Hollywood, the cinema and show business; American reception of Spanish art and culture.